How Does Immigration Fit into the Future of the U.S. Labor Market? - Pia M. Orrenius; Madeline Zavodny; Stephanie Gullo (Institute of Labor Economics (IZA), 2020)
U.S. GDP growth is anticipated to remain sluggish over the next decade, and slow labor force growth is a key underlying reason. Admitting more immigrants is one way U.S. policymakers can bolster growth in the workforce and the economy. A larger role for immigrant workers also can help mitigate other symptoms of the economy's long-run malaise, such as low productivity growth, declining domestic geographic mobility, and falling entrepreneurship, as well as help address the looming mismatch between the skills U.S. employers want and the skills U.S. workers have. While some might argue that technological change and globalization mean there is less need to admit immigrant workers, such arguments fail to account for both recent data and historical experience. Of course, immigration—like anything else—is not without costs, which are disproportionately borne by the least educated. A plan to increase employment-based immigration as a way to spur economic growth could be paired with new programs to help low-skilled U.S. natives and earlier immigrants so that the benefits of immigration are shared more equitably.
Keywords: J61; J15; J18; 330; U.S. immigration policy; labor market trends